Marker-Independent Monitoring of in vitro and in vivo Degradation of Supramolecular Polymers Applied in Cardiovascular in situ Tissue Engineering - Marzi, Julia; Munnig Schmidt, Emma C.; Brauchle, Eva M.; Wissing, Tamar B.; Bauer, Hannah; Serrero, Aurelie; Söntjens, Serge H. M.; Bosman, Anton W.; Cox, Martijn A. J.; Smits, Anthal I. P. M.; Schenke-Layland, Katja (Frontiers in Cardiovascular Medicine, 2022)
The equilibrium between scaffold degradation and neotissue formation, is highly essential for in situ tissue engineering. Herein, biodegradable grafts function as temporal roadmap to guide regeneration. The ability to monitor and understand the dynamics of degradation and tissue deposition in in situ cardiovascular graft materials is therefore of great value to accelerate the implementation of safe and sustainable tissue-engineered vascular grafts (TEVGs) as a substitute for conventional prosthetic grafts. In this study, we investigated the potential of Raman microspectroscopy and Raman imaging to monitor degradation kinetics of supramolecular polymers, which are employed as degradable scaffolds in in situ tissue engineering. Raman imaging was applied on in vitro degraded polymers, investigating two different polymer materials, subjected to oxidative and enzymatically-induced degradation. Furthermore, the method was transferred to analyze in vivo degradation of tissue-engineered carotid grafts after 6 and 12 months in a sheep model. Multivariate data analysis allowed to trace degradation and to compare the data from in vitro and in vivo degradation, indicating similar molecular observations in spectral signatures between implants and oxidative in vitro degradation. In vivo degradation appeared to be dominated by oxidative pathways. Furthermore, information on collagen deposition and composition could simultaneously be obtained from the same image scans. Our results demonstrate the sensitivity of Raman microspectroscopy to determine degradation stages and the assigned molecular changes non-destructively, encouraging future exploration of this techniques for time-resolved quality assessment of in situ tissue engineering processes.